Kajian Pencantuman Keterangan Kedaluwarsa pada Label Pangan Olahan - Dyah Setyowati; Lies Sugiarti (Badan Pengawas Obat dan Makanan, 2022)
Expiration date is one of the information that is mandatory to be included on the processed food label. Indonesia regulates the inclusion of expiration dates with the term